Selected Works of Terry Speed - Dudoit, Sandrine; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The purpose of this volume is to provide an overview of Terry Speed$1 (Bs contributions to statistics and beyond. Each of the fifteen chapters concerns a particular area of research and consists of a commentary by a subject-matter expert and selection of representative papers. The chapters, organized more or less chronologically in terms of Terry$1 (Bs career, encompass a wide variety of mathematical and statistical domains, along with their application to biology and medicine. Accordingly, earlier chapters tend to be more theoretical, covering some algebra and probability theory, while later chapters concern more recent work in genetics and genomics. The chapters also span continents and generations, as they present research done over four decades, while crisscrossing the globe. The commentaries provide insight into Terry$1 (Bs contributions to a particular area of research, by summarizing his work and describing its historical and scientific context, motivation, and impact. In addition to shedding light on Terry$1 (Bs scientific achievements, the commentaries reveal endearing aspects of his personality, such as his intellectual curiosity, energy, humor, and generosity.s
Algebra -- Probability -- Sufficiency -- Analysis of Variance -- Cumulants -- Interaction Models -- Asymptotics and Coding Theory -- Applied Statistics and Exposition -- History and Teaching Statistics -- Genetic Recombination -- Molecular Evolution -- Statistical Genetics -- DNA Sequencing -- Biological Sequence Analysis -- Microarray Data Analysis.
Keywords: Statistics; Mathematical statistics; Statistics; Statistical Theory and Methods